2013
DOI: 10.1007/s11425-013-4752-4
|View full text |Cite
|
Sign up to set email alerts
|

Strictly nonnegative tensors and nonnegative tensor partition

Abstract: In this paper, we introduce a new class of nonnegative tensors -strictly nonnegative tensors. A weakly irreducible nonnegative tensor is a strictly nonnegative tensor but not vice versa. We show that the spectral radius of a strictly nonnegative tensor is always positive. We give some sufficient and necessary conditions for the six well-conditional classes of nonnegative tensors, introduced in the literature, and a full relationship picture about strictly nonnegative tensors with these six classes of nonnegati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 19 publications
2
71
0
Order By: Relevance
“…We say that the tensor A is weakly reducible if its representation R(A) is a reducible matrix. If A is not weakly reducible, then it is called weakly irreducible [12,16].…”
Section: A = Si − B Where S > 0 and B Is A Nonnegative Matrix For Wmentioning
confidence: 99%
See 1 more Smart Citation
“…We say that the tensor A is weakly reducible if its representation R(A) is a reducible matrix. If A is not weakly reducible, then it is called weakly irreducible [12,16].…”
Section: A = Si − B Where S > 0 and B Is A Nonnegative Matrix For Wmentioning
confidence: 99%
“…Since then, much work has been done in spectral theory of tensors. In particular, theory of, and algorithms for calculating, eigenvalues of nonnegative tensors are well developed [6,7,8,12,16,18,19,23,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Qi [18,19] extended some nice properties of symmetric matrices to higher order symmetric tensors. The Perron-Frobenius theorem of nonnegative matrices had been generalized to higher order nonnegative tensors under various conditions by Chang, Pearson and Zhang [5], Hu, Huang and Qi [8], Yang and Yang [26,27], Zhang [28] and others.…”
Section: Preliminaries and Basic Factsmentioning
confidence: 99%
“…Subsequently, these topics attract attention of many mathematicians from different disciplines. For diverse studies and applications on these topics, see Chang [4], Chang, Pearson and Zhang [5], Chang, Pearson and Zhang [6], Hu, Huang and Qi [8], Hu and Qi [7], Ni, Qi, Wang and Wang [15], Ng, Qi and Zhou [16], Song and Qi [23,24], Yang and Yang [26,27], Zhang [28], Zhang and Qi [29], Zhang, Qi and Xu [30] and references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Qi gave the linear convergence of the NQZ method for essentially positive tensors in [16]. Hu, Huang, and Qi [17] established the global R-linear convergence of the modified version of the NQZ method for nonnegative weakly irreducible tensors which were introduced by Friedland, Gaubert, and Han in [18]. Chen, Qi, Yang, et al showed an inexact power-type algorithm for finding spectral radius of nonnegative tensors in [19].…”
Section: Introductionmentioning
confidence: 99%